2011
DOI: 10.1021/jf2020057
|View full text |Cite
|
Sign up to set email alerts
|

Re-formation of Fibrils from Hydrolysates of β-Lactoglobulin Fibrils during in Vitro Gastric Digestion

Abstract: In this study, in vitro digestion of β-lactoglobulin (β-Lg) fibrils and the re-formation of fibril-like structures after prolonged enzymatic hydrolysis (up to 48 h) were investigated using matrix-assisted laser desorption/ionization mass spectrometry (MALDI-MS), thioflavin T fluorescence photometry, and transmission electron microscopy (TEM). Pure β-Lg fibrils that had been formed by heat treatment at pH 2.0 were rapidly hydrolyzed by pepsin in the simulated gastric fluid (pH 1.2), and some new peptides that w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…Hydrolysis and reaggregation were supposed as a synchronous process. Equilibrium existed between the dissociation of the peptides from the original fibrils and the self‐assembly of β ‐lactoglobulin peptides into the new fibrils after pepsin treatment (Bateman et al ., ). However, the reforming mechanism of β ‐conglycinin fibrils was somewhat different from that of β ‐lactoglobulin fibrils.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrolysis and reaggregation were supposed as a synchronous process. Equilibrium existed between the dissociation of the peptides from the original fibrils and the self‐assembly of β ‐lactoglobulin peptides into the new fibrils after pepsin treatment (Bateman et al ., ). However, the reforming mechanism of β ‐conglycinin fibrils was somewhat different from that of β ‐lactoglobulin fibrils.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that amyloid fibrils formed from bovine milk derived b-lactoglobulin are readily digested in vitro by pepsin (Bateman, Ye, & Singh, 2010) and that the hydrolysates themselves are able to reform new fibrils with different morphologies (Bateman, Ye, & Singh, 2011). These intriguing results stand in some contrast to one of the hallmarks of true amyloid fibrils, that is the high resistance towards hydrolysis by proteases such as trypsin and Proteinase K (Watts et al, 2011).…”
Section: Abbreviationsmentioning
confidence: 99%
“…In addition, the increase in aggregate size detected using nanopore detection is in good agreement with literature. [13] The pepsin cleaves highly hydrophobic amino acid and aromatic amino acid residues of β-lactoglobulin amyloid (e.g., leucine, isoleucine, phenylalanine, valine, and tryptophan). It also has a preferential tendency toward the cleavage of peptide bonds adjacent to leucine residues, that is, LX (or XL) bonds.…”
Section: Pepsin Enzymatic Degradation Of β-Lactoglobulin Amyloidsmentioning
confidence: 99%